Assessing Dentinal Microcracks using Micro-CT after Root Canal Preparation with Different Rotary Endodontic File Systems - Mohammed Mustafa; Kailash Attur; Sidharth S. Menon; Shylaja Attur (Journal of Pharmacy and Bioallied Sciences)
Objective: This study aimed to evaluate the propagation of dentinal microcracks in the mesiobuccal (MB) and mesiolingual (ML) canals following root canal preparation using two different rotary endodontic file systems, TruNatomy (continuous rotation) and MicroMega ONE RECI (reciprocating motion), using micro-computed tomography (micro-CT). Materials and Methods: Fifty freshly extracted human mandibular first and second molars were selected based on specific inclusion criteria. Root canal preparation was confined to the MB and ML canals in mesial roots of mandibular molars (Vertucci Type IV canal configurations) using TruNatomy and MicroMega ONE RECI systems. Pre- and post- preparation scans were taken for all the specimens using micro-CT to identify and measure dentinal microcracks. Statistical analysis was performed using a t-test and Fisher’s exact test, with significance set at P < 0.05. Results: The results indicated no statistically significant differences between the two systems in terms of microcrack formation or propagation. In the ML canal, 8.0% of teeth prepared with TruNatomy and 12.0% with MicroMega ONE RECI exhibited microcracks (P = 0.643). In the MB canal, microcracks were found in 12.0% of the TruNatomy group and 8.0% of the MicroMega ONE RECI group (P = 0.643). Both systems showed a significant increase in canal volume, but no significant differences between the instruments (P < 0.001). Conclusion: Both TruNatomy and MicroMega ONE RECI demonstrated similar outcomes regarding dentinal microcrack formation and propagation in the MB and ML canals, with no significant differences. Both systems were effective in enlarging the canals while preserving the natural canal anatomy. These findings suggest that the choice of instrumentation system can be guided by clinical ease and efficiency as both systems offer comparable mechanical effects on dentin integrity during root canal preparation.